Analisis Yuridis Sistem Baru Dalam Pembuktian Terhadap Dokumen Elektronik Pada Perkara Perdata - Harahap, Lia Adetia; Lubis, Fauziah (Ilmu Hukum Prima (IHP), 2024)
The existence of electronic documents as a system of evidence that is increasingly prevalent is a challenge for the Indonesian legal system. However, proof of electronic documents still refers to the provisions on proof of conventional documents. This research aims to juridically analyse the new system in proving electronic documents in civil cases. The method used in this research is normative juridical (legal research) and uses a statute approach and conceptual approach. The results of this study indicate that electronic document evidence along with the times is included in the realm of law and justice. This new system allows proof of electronic documents online, digital signatures and metadata can be used to determine the authenticity of documents. The development of a new system in electronic documents has actually been regulated quite a lot in Indonesian legislation, but in the realm of civil procedural law there are no provisions governing electronic documents as evidence. This issue is also a problem in civil law, because until now electronic documents have become part of national and international commerce. This is also an expansion of electronic documents as evidence in civil procedure law.